2022
DOI: 10.1038/s41598-022-05436-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the occupational exposure to blood-borne pathogens of staff at a third-class specialist hospital in 2015–2018: a retrospective study

Abstract: To understand the current situation of occupational exposure to blood-borne pathogens in a women's and children's hospital and analyze the causes to provide a scientific basis for improving occupational exposure prevention and control measures. We analyzed occupational exposure to blood-borne pathogens in a third-class women's and children's hospital from 2015 to 2018, considering the workers’ occupational categories and length of service; the sites, types, and causes of exposure; and the pathogens of the sour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Recently conducted studies in Bosnia and Herzegovina (19) , Serbia (26) and China (27) show that many studies that investigated incidents of blood exposures showed some significant differences in prevalence between different professional groups. As an example a study in China in the period from 2015-2018 year proved that nurses are in greater risk of exposure of blood-transfer infections (28) , while other studies in Serbia, India and Jamaica proved a greater risk of exposure among physicians (26,29,30) . Also, the profile of the nurses/ technicians did not prove to be a predictor for the occurrence of professional exposure to blood and body fluids transmissible infections.…”
Section: Discussionmentioning
confidence: 99%
“…Recently conducted studies in Bosnia and Herzegovina (19) , Serbia (26) and China (27) show that many studies that investigated incidents of blood exposures showed some significant differences in prevalence between different professional groups. As an example a study in China in the period from 2015-2018 year proved that nurses are in greater risk of exposure of blood-transfer infections (28) , while other studies in Serbia, India and Jamaica proved a greater risk of exposure among physicians (26,29,30) . Also, the profile of the nurses/ technicians did not prove to be a predictor for the occurrence of professional exposure to blood and body fluids transmissible infections.…”
Section: Discussionmentioning
confidence: 99%
“…The main bloodborne infection that causes occupational contact of hospital staff is hepatitis B (30.8%), followed by HIV/AIDS (7.5%). In the other 36.3% of cases, the pathogen status of the source patient is uncertain [10] . Dental nurses are exposed to many special sharp instruments, such as needles, scalers, pulp extractors, ultrasonic tips and periodontal probes.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, nurses are involved in frontline work; they directly participate in medical treatment, and the quality of their work is related to patients' medical safety, therapy, and recovery ( 7 ). Previous studies have shown that nurses have a higher occupational exposure rate than doctors ( 8 , 9 ). The job of dental nurses is particular because they are exposed to many special sharp instruments, such as endodontic files and ultrasonic tips.…”
Section: Introductionmentioning
confidence: 99%